1994
DOI: 10.1148/radiology.190.2.8284402
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal diffusion mapping with use of a whole-body echo-planar system.

Abstract: In vivo diffusion measurements of abdominal organs obtained with MR imaging may prove helpful in the identification and classification of abdominal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
160
1
15

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(189 citation statements)
references
References 0 publications
13
160
1
15
Order By: Relevance
“…In contrast, water molecules move more freely in cystic or necrotic tissues and the water protons ADC is defined freely. As a result DWI provides information about cellularity and cellular membrane integrity, and even microcapillary perfusion The development of echoplanar imaging (EPI), a type of fast MRI method, has shown that, diffusion weighted MRI can be used to evaluate abdominal organs 18,19 . The diffusion properties of tissues are related to the interstitial free fluid and amount of permeability.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, water molecules move more freely in cystic or necrotic tissues and the water protons ADC is defined freely. As a result DWI provides information about cellularity and cellular membrane integrity, and even microcapillary perfusion The development of echoplanar imaging (EPI), a type of fast MRI method, has shown that, diffusion weighted MRI can be used to evaluate abdominal organs 18,19 . The diffusion properties of tissues are related to the interstitial free fluid and amount of permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this limitation, DW-MRI was previously only used for brain imaging until the development of fast MRI techniques. The development of echo planar imaging (EPI), one of the fast MRI techniques, eliminated the long imaging time of conventional sequences and the associated artifacts, thus making DW-MRI usable for abdominal examinations (8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) allows visualization of microscopic water diffusion in biological tissues [2][3][4][5] , and has been applied to head and neck lesions. Many researchers have applied echo-planar imaging (EPI) to DWI of head and neck lesions, as well as diagnosis of diseases of the central nerve system.…”
Section: Introductionmentioning
confidence: 99%
“…The ADC can be useful in characterizing both normal and pathological tissue as it reflects microscopic water diffusion and tissue perfusion in biologic tissues [2][3][4][5] . In many studies, linear regression and gradient b factors of 0 and 1000 sec/mm 2 have been applied to ADC measurement [7][8][9][11][12][13][14]17,18 .…”
Section: Introductionmentioning
confidence: 99%